Impact of extended-release quetiapine fumarate on hospitalization length and cost in schizophrenia and bipolar disorder patients: a retrospective, hospital-based, US-cohort analysis. (July 2014) - Locklear, Julie C; Wahlqvist, Peter; Gustafsson, Urban; Udd, Mattias; Fajutrao, Liberty; Eriksson, Hans
Aim: The aim was to evaluate the impact of quetiapine extended release (XR) on hospitalization length and cost in schizophrenia or bipolar disorder, versus quetiapine immediate release (IR), using Premier Perspective™ inpatient hospital database data.Methods: Inpatient discharges classified within diagnosis-related group 430 (psychoses), prescribed quetiapine XR or IR, were identified. Patients had International Classification of Disease-9 diagnosis of schizophrenia or bipolar disorder. The impact of the XR formulation on hospitalization length and costs was assessed using generalized linear model analyses.Results: A total of 30, 429 discharges between 1 January 2008 and 30 June 2009 were analyzed. Patients who received quetiapine XR had significantly reduced hospitalization length (10.73% estimated reduction; p = 0.001) and cost (9.52% estimated reduction; p < 0.001), versus IR. This corresponds to a 1.0-day reduction in hospitalization (10.73% of 9.2 days) and US532 reduction in hospitalization cost (9.52% of US5588) per patient, based on least squares mean estimations. Evaluation of patient subpopulations suggested the reduction in length of hospitalization for quetiapine XR versus IR was driven mainly by patients with bipolar disorder, whereas cost reduction was driven mainly by patients with schizophrenia.Conclusion: Inpatient use of quetiapine XR in schizophrenia or bipolar disorder is associated with reduced hospitalization length and cost, possibly due to the faster titration schedule versus quetiapine IR.